Establishment of a 10-ha permanent plot in Ayer Hitam Forest Reserve, Selangor - Saari, Nurul Shida; S. M., Shafiq; Ibrahim, Faridah Hanum (Faculty of Forestry, Universiti Putra Malaysia, 2013)
Generally, the establishment of permanent plots is for obtaining long-term data on plant diversity, forest dynamics and demography of species. A 10-ha permanent plot in Ayer Hitam Forest Reserve (AHFR) was established to meet these purposes. Completed in October 2012, the plot establishment started with site selection, boundary marking and assignment of quadrat numbers following standard procedures and protocols. Gathering of the plant inventory involved tree measurements, tagging, marking, mapping and sample collection.